2020
DOI: 10.3390/math8111952
|View full text |Cite
|
Sign up to set email alerts
|

Improving Food Supply Chain Management by a Sustainable Approach to Supplier Evaluation

Abstract: Increasing food supply chain sustainability means having to deal with many conflicting aspects and involves producers, several departments in distribution companies, and consumers. The objectives of this research are to develop models to solve real-world supplier evaluation problems and validate them with real data on fresh fruits in a supermarket chain. Literature review and results from a survey with managers from purchasing, logistics, and quality departments of a food distribution company are used to estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The significance of sorting problems is shown both in the growing number of articles with new methods and fields of application over the last decade (Alvarez et al, 2021). The need to assign alternatives to classes predefined and preference-ordered appears in scenarios related to supplier selection and supplier management (Araz and Ozkarahan, 2007;Barrera et al, 2022;Segura et al 2020). In addition, Chai and Ngai (2020) highlighted sorting technique adoption as one of the main trends for future research in supplier selection.…”
Section: Methods For Supplier Sorting: Literature Reviewmentioning
confidence: 99%
“…The significance of sorting problems is shown both in the growing number of articles with new methods and fields of application over the last decade (Alvarez et al, 2021). The need to assign alternatives to classes predefined and preference-ordered appears in scenarios related to supplier selection and supplier management (Araz and Ozkarahan, 2007;Barrera et al, 2022;Segura et al 2020). In addition, Chai and Ngai (2020) highlighted sorting technique adoption as one of the main trends for future research in supplier selection.…”
Section: Methods For Supplier Sorting: Literature Reviewmentioning
confidence: 99%
“…A large number of articles have studied the problem of profit coordination between manufacturers and retailers in the supply chain, and have designed a variety of coordination mechanisms to maximize the profits of the supply chain, but only a small number of articles have included the consumers who determine product sales in the model and considered the influence of consumer mentality factors even less. Segura et al [40] found that bargaining power is the most important determinant of the relationship between core and upstream and downstream firms in the food supply chain, and the researchers studied the bargaining process between firms in the food supply chain by applying game bargaining theory. Denver et al [41] studied 149 companies at the core of the supply chain, and pointed out that companies in large industries with high uncertainty have begun to pay attention to and implement guidance, education, evaluation, and guidance on green suppliers.…”
Section: Organic Food Supplymentioning
confidence: 99%
“…Accordingly, many review papers have been published on this topic with various areas of focus. Increasing food supply chain sustainability means dealing with many conflicting aspects involving producers, several distribution company departments, and consumers (Segura et al 2020 ). Supply chain sustainability refers to the transparent integration and achievement of organizations’ social, environmental, and economic goals through the effective coordination of internal organizational processes.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%